About The Individual And Social Values In The Works Of Haci Bektash Veli - Duran, Hamiye (Journal of Alevism-Bektashism Studies, 2010)
There are both individual and social problems in our society, and it can be observed that humane val- ues have been weakening in parallel with the decrease in the number of morally upright and virtuous people. As everyone knows, perfect individuals form perfect societies. We also know that the aim of Sufism is to raise people who are called "kamil insan" (perfect man) and who works for God among people. When Hacı Bektash Veli's works are considered from this perspective, it can be observed that there is an abundant number of elements which help individuals become morally and ethically perfect. In Veli's works, there are some individual values such as respect, fear, 'perhizgerlik' (eating less), toleration, the feeling of shyness, generosity, science, modesty, wisdom, and 'marifet' (being virtuous) as well as the social values such as 'haram' (the things forbidden by religion), 'helal' (the things allowed by religion), ordering the good, giv- ing alms, avoiding the evil, alcohol, fortune-telling, interest, and gambling. Starting from this point, we tries to evaluate Hacı Bektash Veli's Works which are entitled Makalat, Besmele Şerhi ve Makalat-ı Gaybiyye ve Kelimat-ı Ayniye in terms of social and individual values.
Keywords: keyword